Improving Brand Image of Television Electronic Products Through Integrated Marketing Communications - Fitriani Latief (Advances in Business & Industrial Marketing Research, 2023)
This study aims to examine and analyze the effect of integrated marketing communications (advertising, sales promotion, public relations, personal selling, direct & online marketing) on ​​the brand image of electronic television products. The population in this study were 2,576 customers or users of the 2018 Panasonic brand television. To determine the number of samples, the Slovin formula was used and 100 people were obtained spread across the city of Makassar. The data in this study used primary data collected by distributing questionnaires to all respondents. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, validity and reliability tests and testing of all hypotheses through the coefficient of determination test, partial test (t test) and simultaneous test (f test). The results of this study indicate that the variables of advertising, promotion, public relations, personal selling and direct & online marketing have a positive and significant effect on the brand image of television electronic products at PT. Panasonic Goblet. And based on the test results on all variables in the integrated marketing communication program, the promotion variable has the most dominant value influencing the brand image of television electronic products at PT. Panasonic Goblet.